2012
DOI: 10.1084/jem.20111569
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression induced by Toll-like receptors in macrophages requires the transcription factor NFAT5

Abstract: NFAT5 regulates the induction of TLR-stimulated genes with constitutive binding to the Tnf promoter regardless of TLR ligation and recruitment to Nos2 and Il6 dependent on TLR activation and IKKb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
196
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(220 citation statements)
references
References 78 publications
23
196
0
1
Order By: Relevance
“…We report prominent expression of AR, TauT, and SMIT in the perifascicular atrophic fibers of DM, accompanied by increased/induced expression of other known NFAT5 molecular targets HSP70, 27 iNOS, 28 and CCL2. 29 As was the case earlier for iNOS, 30 we could, however, not confirm a significant increase of AR protein levels in DM muscle extracts via western blotting, presumably because of its expression being limited to the affected perifascicular areas.…”
Section: Osmolyte Pathway Activation In Dmmentioning
confidence: 74%
“…We report prominent expression of AR, TauT, and SMIT in the perifascicular atrophic fibers of DM, accompanied by increased/induced expression of other known NFAT5 molecular targets HSP70, 27 iNOS, 28 and CCL2. 29 As was the case earlier for iNOS, 30 we could, however, not confirm a significant increase of AR protein levels in DM muscle extracts via western blotting, presumably because of its expression being limited to the affected perifascicular areas.…”
Section: Osmolyte Pathway Activation In Dmmentioning
confidence: 74%
“…However, we found that RON activity was associated with an overall immunosuppressive state. For example, macrophage genes known to be upregulated by the inflammatory stimulus lipopolysaccharide (LPS) 44 were downregulated in the presence of MSP stimulation ( Fig S3a,b ). Differentially expressed genes in our study were mostly in agreement with findings reported by Chaudhuri et al, who used microarray technology to investigate gene expression changes in macrophages 20 hours after MSP treatment 31 ( Fig S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the broader context, NFAT5-mediated adaptation to hyperosmotic stress is crucial to the development and function of macrophages (45) and lymphocytes (62). The current paradigm of cellular osmotic regulation is focused on the activation of target genes, post-translational modification or other direct interactions of NFAT5, which mediates this program (63)(64)(65)(66)(67).…”
Section: Discussionmentioning
confidence: 99%
“…PU.1 is a critical transcriptional regulator in myelopoiesis (43), and PU.1 target genes harbor binding sites that correspond to high affinity sequences (44). We analyzed differential gene expression in bone marrow-derived macrophages from NFAT5 knock-out mice relative to their isogenic wild type and identified a core set of 24 genes (NCBI GEO accession number GSE26343; adjusted p Ͻ 0.05) (45). We then screened these NFAT5-dependent genes against data sets in which PU.1 or another (control) pro-tein is induced, knocked down, or knocked out in similar cellular backgrounds under resting (unstimulated) conditions (Fig.…”
Section: Pu1 Target Genes Are Enriched Among Genes Thatmentioning
confidence: 99%